Pencatatan Produksi Kusen dan Lemari PD. Daya Jaya Menggunakan Metode Harga Pokok Pesanan - Yulia, Yulia; Rahayuningsih, Panny Agustia; Nadia, Putri; yulia (Jurnal Sistem Informasi Akuntansi, 2024)
Production is a process in which goods or services called inputs are converted into goods or services called outputs. Where the production function shows how much maximum output can be produced if a certain amount of input is used in the production process. The object of research at PD. Daya Jaya, the author examines the production section where the process of calculating production costs used is still less effective. The system created applies the Order Costing Method, where the order costing method is a method that produces based on each order, collecting the cost of production using the order costing method. The methodology used to build this system uses the waterfall method. The programming language used in creating web-based applications consists of hypertext preprocessor (PHP), hypertext markup language (HTML), cascading style sheet (CSS). The results of this study are web-based applications where there are several features in the admin section, there are accounts, raw materials, auxiliary materials, factory overhead, employees, orders, incoming raw materials, incoming auxiliary materials and order history. Then in the production section there is production and in the owner section there is a report feature where the owner can view and print reports